1988
DOI: 10.1002/aoc.590020209
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of butyltin compounds in oyster samples

Abstract: Experimental instrumentation for the speciation of butyltin compounds by hydride generation and gas chromatographyquartz furnace atomic absorption spectrometry is described. Evaluation of a number of extraction methods revealed that simple acid leaching of oyster samples gave adequate recoveries. The levels of each butyltin species in oyster flesh and gill are reported together with the tentative identification of a mixed methylbutyltin compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Volatile butylmethyltin compounds formed by biomethylation were reported in the 1980s by Maquire and coworkers 84,85 and Rapsomanikis and Harrison, 79 and more recently by Yonezawa et al 83 and Vella and coworkers. 82,86±88 In 1994, Yonezawa et al 83 reported that these biomethylations are one of degradation of the triorganotin compounds by microbial activities in the sediment.…”
Section: Bioaccumulations and Sediment Accumulation On Organotin Antimentioning
confidence: 92%
“…Volatile butylmethyltin compounds formed by biomethylation were reported in the 1980s by Maquire and coworkers 84,85 and Rapsomanikis and Harrison, 79 and more recently by Yonezawa et al 83 and Vella and coworkers. 82,86±88 In 1994, Yonezawa et al 83 reported that these biomethylations are one of degradation of the triorganotin compounds by microbial activities in the sediment.…”
Section: Bioaccumulations and Sediment Accumulation On Organotin Antimentioning
confidence: 92%
“…Naturally occurring organotin compounds are mainly biomethylated species generated from inorganic tin (Sn 4+ ) in sediments and estuarine environments. Natural methylation of butyltin compounds has also been reported [59].…”
Section: Speciation Of Tin Compoundsmentioning
confidence: 95%
“…In this study, 5% (v/v) solution was used according to Rapsomanikis et al [10] and Fisher et al [11]. Silylation was performed as follows:…”
Section: Teemu Näykkimentioning
confidence: 99%